Developing a co-culture system for effective megakaryo/thrombopoiesis from umbilical cord blood hematopoietic stem/progenitor cells - Hatami, Javad
Background aims. Platelet transfusion can be a life-saving procedure in different medical settings. Thus, there is an increasing demand for platelets, of which shelf-life is only 5 days. The efficient ex vivo biomanufacturing of platelets would allow overcoming the shortages of donated platelets. Methods. We exploited a two-stage culture protocol aiming to study the effect of different parameters on the megakaryo/thrombopoiesis ex vivo. In the expansion stage, human umbilical cord blood (UCB)-derived CD34þ-enriched cells were expanded in co-culture with human bone marrow mesenchymal stromal cells (BM-MSCs). The megakaryocytic commitment and platelet generation were studied, considering the impact of exogenous addition of thrombopoietin (TPO) in the expansion stage and a cytokine cocktail (Cyt) including TPO and interleukin-3 in the differentiation stage, with the use of different culture medium formulations, and in the presence/absence of BM-MSCs (direct versus non-direct cell-cell contact). Results. Our results suggest that an early megakaryocytic commitment, driven by TPO addition during the expansion stage, further enhanced megakaryopoiesis. Importantly, the results suggest that coculture with BM-MSCs under serum-free conditions combined with Cyt addition, in the differentiation stage, significantly improved the efficiency yield of megakaryo/thrombopoiesis as well as increasing %CD41, %CD42b and polyploid content; in particular, direct contact of expanded cells with BM-MSCs, in the differentiation stage, enhanced the efficiency yield of megakaryo/thrombopoiesis, despite inhibiting their maturation. Conclusions. The present study established an in vitro model for the hematopoietic niche that combines different biological factors, namely, the presence of stromal/accessory cells and biochemical cues, which mimics the BM niche and enhances an efficient megakaryo/thrombopoiesis process ex vivo.